2021
DOI: 10.1055/s-0041-1727556
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chlorhexidine Modified Cement in Orthodontic Patients: A Double-Blinded, Randomized, Controlled Trial

Abstract: Objectives The aim of this study was to evaluate the microbiological and mechanical properties of glass ionomer cement (GIC) modified by chlorhexidine (CLX) for the purpose of cementing bands to the teeth of orthodontic patients. Materials and Methods Ten patients, between the ages of 19 and 33 years, in the initial stage of orthodontic treatment, were randomly designated to two groups using the split-mouth design (n = 10). One group (GICEX) had bands cemented with GIC modified by CLX and a Control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The addition of antibacterial agents was expected to reduce biofilm colonization around orthodontic brackets. Studies have shown that the addition of chlorhexidine into orthodontic cements enhances antibacterial actions without affecting the bonding performance 19 , 20 . However, severe allergic reactions to chlorhexidine have remained a major concern 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of antibacterial agents was expected to reduce biofilm colonization around orthodontic brackets. Studies have shown that the addition of chlorhexidine into orthodontic cements enhances antibacterial actions without affecting the bonding performance 19 , 20 . However, severe allergic reactions to chlorhexidine have remained a major concern 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Various antibacterial fillers were incorporated into the adhesives, such as chlorhexidine [16] to promote the antibacterial actions of the materials. The concerns with chlorhexidine are the risk of causing a severe allergic reaction [17,18] and the development of antibiotic resistance [19,20], which is a current global health threat.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of CHX into GICs generated a cytotoxic potential in the short term, was capable of causing tissue damage by inflammation, which reduced the rapid healing response. This suggested that because of its substantivity, the CHX released at the GIC surface may have had an antibacterial effect, as a result of the superficial erosion (Hoszek & Ericson, 2008) that allowed bacterial inhibition (Lessa et al, 2010; Rolla & Melsen, 1975), which was reinforced in the analysis over time (Araújo et al, 2021). Clinical experiments with humans could check the efficacy of what appears to be a notoriously promising method for formulating a GIC with antibacterial efficacy for cementing purposes.…”
Section: Discussionmentioning
confidence: 99%